Mortality in children and adolescents with autoimmune inflammatory rheumatic diseases admitted to the pediatric intensive care unit - Tinnapat Buranapattama; Suwannee Phumeetham; Nuntawan Piyaphanee; Maynart Sukharomana; Sirirat Charuvanij (Pediatric Rheumatology Online Journal)
Abstract Background This study aimed to describe the characteristics and outcomes of children and adolescents with autoimmune inflammatory rheumatic diseases (AIIRD) who were admitted to the pediatric intensive care unit (PICU). The accuracy of the Pediatric Risk of Mortality (PRISM) III and Pediatric Index of Mortality (PIM) 3 scores to predict the mortality were investigated. Methods This was a retrospective cohort study. Children and adolescents with AIIRD aged ≤ 18 years who were admitted to the PICU at the largest university-based referral center in Thailand during July 2011 to June 2021 were included. Results There were 122 PICU admissions from 74 patients; mean age of 12.0 ± 4.3 years, 74.3% female. Majority of AIIRD were systemic lupus erythematosus (SLE) (83.8%), followed by systemic juvenile idiopathic arthritis (5.4%), juvenile dermatomyositis (JDM) (2.7%) and microscopic polyangiitis (2.7%). The main cause of admission was combined infection and disease flare (29.5%). Pneumonia was the main site of infection. Acinetobacter baumanii was the most common causative agent. Macrophage activation syndrome occurred in 8 (6.5%) admissions. The mortality rate of PICU admissions was 14.8% from 18 deaths; 17 with SLE and 1 with JDM. Mechanical ventilation (aOR 24.07, 95%CI:1.33-434.91, P= 0.031), pneumothorax (aOR 24.08, 95%CI:1.76-328.86, P = 0.017 and thrombocytopenia (aOR 8.34, 95%CI:1.31–53.73, P = 0.025) were associated with mortality. The risk of mortality rate as predicted by the PRISM III score increased with a score ≥ 9. For the PIM 3 score, the risk of mortality increased if the score ≥ 3. The area under the ROC curve for the PRISM III and PIM 3 scores was 0.741 (95%CI: 0.633–0.849), P = 0.001 and 0.804 (95%CI: 0.685–0.924), P < 0.001, respectively. The model calibration using the Hosmer-Lemeshow goodness of fit test demonstrated a chi-square of 4.335, P = 0.826 for PRISM III and 7.987, P = 0.435 for PIM 3. Conclusion SLE was the main AIIRD that required admission to the PICU. Mechanical ventilation, pneumothorax and thrombocytopenia were associated with mortality in pediatric patients with AIIRD. The PRISM III and PIM 3 scores demonstrated good calibration, while the PIM 3 score provided better discrimination ability in the prediction of mortality for pediatric AIIRD.